Association of Peri-ictal Brainstem Posturing With Seizure Severity and Breathing Compromise in Patients With Generalized Convulsive Seizures. (19th January 2021) - Vilella, Laura; Lacuey, Nuria; Hampson, Johnson P.; Zhu, Liang; Omidi, Shirin; Ochoa-Urrea, Manuela; Tao, Shiqiang; Rani, M.R. Sandhya; Sainju, Rup K.; Friedman, Daniel; Nei, Maromi; Strohl, Kingman; et al.
Abstract : Objective: To analyze the association between peri-ictal brainstem posturing semiologies with postictal generalized electroencephalographic suppression (PGES) and breathing dysfunction in generalized convulsive seizures (GCS). Methods: In this prospective, multicenter analysis of GCS, ictal brainstem semiology was classified as (1) decerebration (bilateral symmetric tonic arm extension), (2) decortication (bilateral symmetric tonic arm flexion only), (3) hemi-decerebration (unilateral tonic arm extension with contralateral flexion) and (4) absence of ictal tonic phase. Postictal posturing was also assessed. Respiration was monitored with thoracoabdominal belts, video, and pulse oximetry. Results: Two hundred ninety-five seizures (180 patients) were analyzed. Ictal decerebration was observed in 122 of 295 (41.4%), decortication in 47 of 295 (15.9%), and hemi-decerebration in 28 of 295 (9.5%) seizures. Tonic phase was absent in 98 of 295 (33.2%) seizures. Postictal posturing occurred in 18 of 295 (6.1%) seizures. PGES risk increased with ictal decerebration (odds ratio [OR] 14.79, 95% confidence interval [CI] 6.18–35.39, p < 0.001), decortication (OR 11.26, 95% CI 2.96–42.93, p < 0.001), or hemi-decerebration (OR 48.56, 95% CI 6.07–388.78, p < 0.001). Ictal decerebration was associated with longer PGES ( p = 0.011). Postictal posturing was associated with postconvulsive central apnea (PCCA) ( p = 0.004), longer hypoxemia ( p < 0.001), and SpO2 recovery ( p = 0.035). Conclusions: Ictal brainstem semiology is associated with increased PGES risk. Ictal decerebration is associated with longer PGES. Postictal posturing is associated with a 6-fold increased risk of PCCA, longer hypoxemia, and SpO2 recovery. Peri-ictal brainstem posturing may be a surrogate biomarker for GCS severity identifiable without in-hospital monitoring. Classification of Evidence: This study provides Class III evidence that peri-ictal brainstem posturing is associated with the GCS with more prolonged PGES and more severe breathing dysfunction.